Methods for Determination of Antimicrobial Activity of Essential Oils In Vitro-A Review - Hulankova, Radka (Plants (Basel, Switzerland), 2024)
Essential oils (EOs) have been gaining popularity in the past decades among researchers due to their potential to replace conventional chemicals used in the fight against pests, pathogenic and spoilage microbes, and oxidation processes. EOs are complex mixtures with many chemical components, the content of which depends on many factors-not just the plant genus, species, or subspecies, but also chemotype, locality, climatic conditions, phase of vegetation, method of extraction, and others. Due to this fact, there is still much to study, with antimicrobial effect being one of the key properties of EOs. There are many methods that have been frequently used by researchers for in vitro evaluation; however, although the research has been going on for decades, an internationally accepted standard is still missing. Most of methods are based on time-proven standards used for the testing of antibiotics. Due to the specific properties of EOs and their components, such as volatility and hydrophobicity, many modifications of these standard procedures have been adopted. The aim of this review is to describe the most common methods and their modifications for the testing of antimicrobial properties of EOs and to point out the most controversial variables which can potentially affect results of the assays.
Keywords: agar diffusion; agar dilution; vapor phase; broth dilution; biofilm; plant extracts; antibacterial